Character Educational Values in The Movie “Turning Red” and its Implication Toward Character Education of Young Learners - Jehan Ayu Mentari; Masagus Firdaus; Hanni Yukamana (Departement of Mathematics Education, 2024)
This case study looks at the function of movies in educational character, specifically the animated feature